Navigating the Antenna Frontier for Emerging IoT Technologies - IR. Kazi Kutubuddin Sayyad Liyakat (International Journal of VLSI Circuit Design & Technology, 2025)
Internet of Things (IoT) is rapidly transitioning from niche applications to a pervasive, interconnected fabric of intelligent devices, demanding unprecedented levels of performance, reliability, and miniaturization from its constituent components. At the heart of this revolution lies the antenna, the crucial interface between the digital and physical realms. This paper delves into the intricate and evolving landscape of IoT antenna design, specifically addressing the unique challenges and opportunities presented by emerging technologies. The constantly changing IoT antenna design landscape is thoroughly examined in this study, with a focus on the difficulties and new possibilities related to next-generation technology. We examine how low- power wide-area network (LPWAN) protocols like Lora WAN and NB-IoT, as well as contemporary wireless technologies like 5G and 6G, affect antenna design characteristics. Changes in operating frequency, bandwidth requirements, radiation efficiency, angular coverage, and the requirement for multipurpose capabilities are some of these. The development of tiny, highly integrated antennas that maintain strong performance under severe form-factors and power constraints is becoming more and more important as small, battery-operated Internet of Things devices proliferate. We explore the impact of technologies such as 5G/6G, Lora WAN, NB-IoT, and the proliferation of miniaturized, energy-constrained devices on antenna form factors, bandwidth requirements, and radiation efficiency. Furthermore, we investigate novel materials, advanced simulation techniques, and innovative design paradigms, including reconfigurable, AI-driven, and integrated antenna solutions, that are essential for overcoming current limitations. The objective is to provide a comprehensive overview of the state-of-the-art, identify critical research gaps, and outline future directions for optimizing antenna performance to unlock the full potential of the next generation of IoT applications, ranging from ubiquitous sensing and smart infrastructure to immersive extended reality and sophisticated industrial automation.
Keywords: Antenna; Bandwidth; Form factor; IOT; multiband